Mental Health as a Determinant of Academic Performance among Students of Emmanuel Alayande College of Education, Oyo, Nigeria - Rafat Bukola Dauda; Abdulkarim Olatunji Abdulkadir (Fenomena, 2025)
Mental health plays a crucial role in students’ academic and social lives. However, while global and regional studies have explored the prevalence of stress, anxiety, and depression among university students, limited research has examined how these factors specifically influence academic performance in Nigerian colleges of education. This study addresses that gap by investigating mental health as a determinant of academic performance among Emmanuel Alayande College of Education (EACOED) students in Nigeria. A cross-sectional survey design was employed with a purposive sample of 366 students, and data were collected through a structured questionnaire. Descriptive statistics, Pearson correlation, and regression analysis were applied. The results show that academic stress and financial hardship are the strongest predictors of depression, while excessive technology use significantly increases stress and anxiety. Importantly, a moderate negative correlation (r = –0.54, p < 0.05) was found between psychological distress and academic performance, confirming that poor mental health directly reduces students’ academic outcomes. The study makes a novel contribution by demonstrating that, unlike in previous African and Asian studies where family expectations and social support were central, academic and financial stressors are more critical in this Nigerian college context. It concludes that mental health literacy and proactive institutional interventions—such as campus-based counselling units, financial support schemes, and digital wellness programs—are essential for improving student well-being and academic success.